Mitochondria-targeting Pt/Mn porphyrins as efficient photosensitizers for magnetic resonance imaging and photodynamic therapy. (July 2019) - Yang, Mengqian; Deng, Jingran; Guo, Ding; Sun, Qi; Wang, Zejiang; Wang, Kai; Wu, Fengshou
Abstract: Photodynamic therapy (PDT), as a minimally invasive and highly efficient anticancer approach, has received extensive attention. However, the search for more effective and less toxic photodynamic photosensitizers with good biocompatibility and high specificity are still highly expected. Herein, we synthesized and characterized a new porphyrin-based photosensitizer Pt-MnPor-PPh3, which integrated the magnetic resonance imaging (MRI) and fluorescence diagnostics and mitochondrial-targeted photodynamic therapy. The cell viabilities reduced with the increase of photosensitizer dose. The IC50 of Pt-MnPor-PPh3 was calculated to be 30.74 μg/mL under light irradiation for 10 min. In contrast, the cell viabilities of the control group, HeLa cells treated without laser irradiation, were still over 80% even at 50 μg/mL of Pt-MnPor-PPh3 . The cellular uptake and subcellular localization of the conjugate were further evaluated through a confocal laser scanning microscope. The results showed that the conjugate had good mitochondrial-targeted properties in the cancer cells. Moreover, the presence of paramagnetic metal Mn ions in Pt-MnPor-PPh3 endowed them with good MRI performances, which provided a feasible synthetic strategy to develop new medicines for MRI-guided and organelle-targeted PDT applications in cancer theranostics. Highlights: Porphyrin-based photosensitizer Pt-MnPor-PPh3 was synthesized and characterized. Pt-MnPor-PPh3 integrated the MRI and fluorescence diagnostics. Pt-MnPor-PPh3 could be used as mitochondria-targeted PDT for cancer cells.